City of dust : illness, arrogance and 9/11 Anthony Depalma. - DePalma, Anthony (FT Press, 2011)
Examines the effects of the dust and ash caused by the towers collapsing on September 11, 2001, in New York, discusses other possible health and environmental issues that could occur, and recounts how the aftermath was treated politically